Implementing the ALI Level 1 Pra Tilawah Method to Enhance Tahsin Ability in Beginner Santri: A Case Study at Pondok Pesantren Assalam Al-Islami, Musi Banyuasin - Didi Hardi Saputra; Ismail Fahri (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This study examines the implementation of the ALI Level 1 Pra Tilawah method in improving the tahsin ability of beginner santri at Pondok Pesantren Assalam Al-Islami Sungai Lilin, Musi Banyuasin. Prior to this study, tahsin learning at the institution relied on the Ummi method, which proved insufficiently adaptive to the heterogeneous baseline abilities of beginner students, resulting in persistent recitation errors particularly in makhraj al-huruf and sifat al-huruf. This study employs a qualitative approach with a case study design. Data were collected through non-participatory observation, semi-structured in-depth interviews, and documentation, and analyzed using the interactive model of Miles and Huberman. Trustworthiness was ensured through source and technique triangulation as well as member checking. The findings reveal three principal outcomes: first, the ALI Level 1 Pra Tilawah method was implemented systematically through planning, implementation, and evaluation stages centered on talaqqi-based phonetic drills and direct corrective feedback; second, supporting factors included institutional commitment, instructor qualification, and student motivation, while the primary inhibiting factors were learner heterogeneity and time constraints; third, the method produced measurable improvements in students' makhraj accuracy, sifat al-huruf awareness, and overall recitation quality. These findings suggest that the ALI Level 1 Pra Tilawah method offers an effective and replicable pedagogical framework for foundational Qur'anic tahsin instruction in pesantren settings.